(untitled) (International journal of artificial intelligence, 2025)
The article presents a comparative analysis of linguocultural units in the Uzbek and Tajik languages. Linguoculturology, as a scientific field, examines cultural and spiritual values reflected in language. The study analyzes such concepts as mother, bread, hospitality, labour, nature, animal imagery, ritual expressions, religious values, love and loyalty, and metaphorical constructions. The findings indicate that due to the historical closeness of the two nations, many similarities exist, but national specificities remain in ritual and everyday expressions.